Pengembangan Media Pembelajaran Visual Berbasis Teknologi (AR) Augmented Reality Mata Pelajaran IPAS Materi Indonesiaku Kaya Budaya Untuk Siswa Kelas IV SDN 1 Tambaksogra - Salsabilla Shofia Azizah; Pamujo Pamujo (Journal on Education, 2024)
The low level of student participation in the teaching and learning process can be attributed to teachers' limited use of learning media in the classroom. This finding is based on observations conducted by the researcher in the fourth grade at SDN 1 Tambaksogra. The insufficient engagement of students in learning leads to a lack of comprehension of the lessons delivered by the teacher. This study aims to support the teaching process in elementary schools by developing visual learning media using augmented reality. Specifically, it focuses on the subject of natural and social science (IPAS). This research aims to create an interactive and user-friendly augmented reality-based visual learning medium that enhances student participation and facilitates a better understanding of the material. The research employs the ADDIE model. Data collection instruments include validation questionnaires from media and material experts, practical response questionnaires from teachers and students, and pre-test and post-test assessments. The results indicate that the developed augmented reality-based media received a score of 98%, signifying high validity. The material expert validation scored 80%, indicating validity. The student response questionnaire scored 95%, categorizing the developed media as highly practical. The pre-test and post-test results yielded an N-Gain score of 0.5, meeting the criteria for effectiveness.